Evaluasi Ciri Fisik Media Terfermentasi Jamur Pleurotus ostreotus sebagai Pakan Ternak Alternatif bagi Ruminansia - Yulia Riska Azzahra; Toto Toharmat; Iwan Prihantoro (Institut Pertanian Bogor, 2022)
By-products such as oil palm empty fruit bunches (EFB), palm kernel cake, and sawdust can be used as alternative feed. It contains nutrients needed by ruminants but is constrained by its high crude fiber content, including lignin, cellulose, and hemicellulose, and is low in protein. This study was conducted to evaluate the physical characteristics of the fermented media from plantation by-products using Pleurotus ostreotus as an alternative to ruminant animal feed. The experimental design was a completely randomized (CRD) with 3'3 factorial patterns with three replications. Factor A was the type of substrate, namely palm kernel cake, EFB, and acacia sawdust. Factor B was the length of fermentation, namely 0, 30, and 60 d. The data collected were analyzed by variance (ANOVA), and the results were significantly different. The observed variables were the mycelium growth rate, media weight, dry matter, organic matter, particle size, specific gravity, pile density, and compacted pile density. We conclude that the fermented sawdust gave the best growth speed of the P. ostreotus mycelia. The palm kernel cake substrate without storage showed good physical quality concerning particle size, pile density, and pile-compaction density. P. ostreotus fungus grew effectively and did not negatively impact the substrates' biomass, dry matter, and organic matter. Different substrate types give different physical characteristics to the P. ostreotus-fermented media. Keywords: acacia, empty fruit bunches, palm kernel cake, fermented media, Pleurotus ostreotus